(3OQ GdhGYXjf hPNQ GdYGHOjfs - (3eMeO Hf SdGeI Hf LYaQ Hf Ydj Hf Mcehf GdbVGYj , TgGH GdOjf CHh YHO Gddg,J (B454 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHg fSJYjf SejJ gPGGdcJGH HOQ GdhGYXje hPNQ GdYGHOjf hgj YTQhf eLdSkG GdeLdS GdChd ai GdEjeGf s
(3BNQgG (B:s
(3aOYG dg HGdHbGA aCeQJ HJCNjQ GdCeQ efg HHQcI UObJg JeJ GdcJGH HYhf Gddg Gdedc GdhgGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSH gPG GdcJGH ddbVGYi hdG JUM fSHJg Edjg dCf ajg fbhdkG Yf GdZRGdi J (B/ 505 (3g` hYf TgGH GdOjf GdSgQhQOi J(B/ 586 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs